Leadership Ethics and Social Responsibility in Education: Advancing Sustainable Development Goal (SDG) 4 in American Schools - Hakeem Ayodeji Nafiu (PAEDAGOGIA, 2025)
This study addressed the challenge of educational disparities in American schools, which hindered equitable access to quality education, a key aim of Sustainable Development Goal (SDG) 4. The objective was to explore how ethical leadership practices fostered fairness, inclusivity, and social responsibility to advance this goal. A qualitative case study design was employed, involving six public schools across urban, rural, and suburban settings in California, Texas, New York, and Ohio. Eighteen participants, comprising principals, teachers, and community stakeholders, provided diverse perspectives. Data were collected through semi-structured interviews conducted via secure online platforms, document analysis of school budgets and strategic plans, and stakeholder surveys distributed electronically. Thematic analysis, guided by a structured six- step process, identified three core themes: equitable resource allocation, inclusive school cultures, and community partnerships. The analysis revealed that ethical leaders prioritized resources for marginalized students, implemented culturally responsive teaching, and built community collaborations to support holistic student needs. These practices created environments where all students could thrive, addressing disparities and promoting lifelong learning. The study concluded that ethical leadership offered a practical framework for advancing SDG 4 by integrating fairness, inclusivity, and community engagement. This framework provided schools with actionable strategies to ensure equitable education, fostering trust and sustainability. The findings contributed to educational leadership literature and offered insights into global education systems aiming to achieve quality education for all.